Managerial and Behavior Education and Training Business Development through Experiential Learning Method - Andi Iswoyo; Didik Daryanto; Wahyu Nugroho (Asian Journal of Innovation and Entrepreneurship, 2017)
Education and training effort Managerial Behavior developed using experience-based education methods (Experiential Learning), which is the process of learning in which learners combining knowledge, skills and values through direct experiences through outdoor activities. Business development goals are to meet the needs of the community-based education and training of the EL. The method of implementation is applied is to maintain the existing condition of raw materials / clients, improve services through the ownership of assets, equipment, understand the needs of clients and supervision, good management, marketing strategy of segmenting and targeting, pricing, promotion, and human resources are adequate. Our operating results have been achieved which is kept to maintain the existence of raw materials / clients, improvement of service procedures, improvement of security procedures, create training modules, the addition of new games, website development company and information management systems training, adjustment of the price of services, developing services such as construction outbound park and camping ground, include employees and facilitators in the training of tax and e-SPT, workshop Facilitating Skill for Rope Courses, workshop First Aid and High Ropes, Certified facilitator and workshops in the other, to develop cooperation with the Asosiasi Experiential Learning Indonesia (AELI) and Himpunan Provider Outbound Indonesia (HPOI), as well as establish business entities Limited Company and register the business brand. The impact was an increase in revenue from year to year.